Percutaneous “Y” biliary stent placement in palliative treatment of type 4 malignant hilar stricture - Corvino, Fabio; Centore, Luca; Soreca, Emilio; Corvino, Antonio; Farbo, Vincenzo; Bencivenga, Alfonso (Journal of Gastrointestinal Oncology; Vol 7, No 2 (April 01, 2016): Journal of Gastrointestinal Oncology, 2015)
Background/aim: This study evaluated the technical and clinical efficacy of percutaneous bilateral biliary stent-in-stent (SIS) deployment technique with a “Y” configuration using open-cell-design stents in type 4 Klatskin tumor patients. Methods: Retrospective evaluation ten patients with type IV Bismuth malignant hilar stricture (MHS) treated with percutaneous bilateral “Y” SIS deployment technique placement followed in our institution between March of 2012 and November of 2014. Results: Bilateral SIS deployment was technically successful in all patients. One patient (10%) had major complications (episode of cholangitis); one patient (10%) had minor complications, including self-limiting hemobilia. Successful internal drainage was achieved in nine (90%) patients. Stent occlusion by tumor overgrowth and sludge formation occurred in two patient (20%). The median survival and stent patency time were 298 and 315 days respectively. Conclusions: Percutaneous bilateral metal stenting using a Y-stent is a valid option for the palliative treatment of type 4 Bismuth MHS, improving quality patient’ life.